Molecular and biochemical analysis of the diet of the black rhinoceros - Kgopa, Ananias Hodi (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2009)
The black rhinoceros, Diceros bicornis, is listed as critically endangered. The black rhinoceros population in the Great Fish River Reserve (GFRR) has increased steadily to a current estimate of one hundred animals since the re-introduction of four animals in 1986. In an effort to contribute to the effective conservation and management of this species, dietary composition was studied in the medium Portulcaria thicket vegetation of the GFRR. This study used a molecular approach to determine the diet of the black rhinoceros of the GFRR by sequencing the ribulose bisphosphate carboxylase large subunit (rbcL) gene in plants and dung. Twenty-three plant species were collected from the reserve, and 802 bp of the rbcL gene were sequenced. These plant sequences were used as a reference database for the identification of plant sequences generated from black rhinoceros dung. Initial studies investigated the amplification, cloning and sequencing of DNA extracted from the dung samples which indicated the viability of the molecular approach. Thereafter, dung generated rbcL DNA was analyzed by GS FLX sequencing. Of the plant sequences identified by comparison to the GenBank database, Carissa bispinosa was the most prevalent. The study further characterized the antioxidant activities and phenolic content of plants eaten by the black rhinoceros using four different assays. Phyllanthus verrucosus, Putterlickia pyracantha, Maytenus capitata, Euclea undulata and Ozoroa mucrunata consistently had high antioxidant activities when assayed against 2,2-azinobis (3-ethyl benzothiazolium-6-sulfonic acid) (ABTSÊ¹â º), 2,2-diphenyl-1-picrylhydrazyl (DPPHÊ¹), and ferric reducing antioxidant potentials (FRAP) and phenolic content when evaluated using the Folin-Ciocalteu assay. The majority of plants investigated showed low antioxidant potentials and low phenolic content. The extent to which antioxidants influenced the browse selection by the black rhinoceros remains inconclusive.
Keywords: Black rhinoceros -- South Africa -- Eastern Cape; Browse (Animal food) -- South Africa -- Eastern Cape -- Analysis; Black rhinoceros -- Manure -- Analysis; Phenols; Antioxidants; Plant ecology -- South Africa -- Eastern Cape